ANALISIS HAMBATAN BELAJAR BAHASA ARAB DI MADRASAH DINIYAH TAKMILIYAH AWALIYAH AINUL ULUM, KECAMATAN SENDURO, KABUPATEN LUMAJANG - Nanda Ayu Pawestri; Abdul Jalil; Atika Zuhrotus Sufiyana (VICRATINA, 2020)
Studying is obligatory for every Muslim, educators an important role in the development of student intelligence. Educators must understand every student, from the easy and difficult, that naturally experienced by students, the situation called a learning obstacle. It experienced by students in Madrasah Diniyah Takmiliyah Awaliyah Ainul Ulum, Kecamatan Senduro, Kabupaten Lumajang. The purpose of this research is to find out the causes of the Arabic learning obstacle; knowing how the role of educators in overcoming the Arabic learning obstacle; and find out solutions for the Arabic learning obstacle. This research uses a qualitative approach with descriptive research. The research was conducted by an in-depth interview by phone. The results showed that the students experienced obstacles in learning Arabic, not memorizing Arabic letters, there was no handbook for students, no interest in learning Arabic, difficult for memorizing Arabic vocabulary, and difficult to pronounce Arabic letters that were appropriate. Educators try to provide additional hours of learning, photocopying textbooks, and providing motivation in overcoming obstacles to learning Arabic. The solution provided was that Arabic learning hours were changed to 14.15-17.30; apply a fee of IDR 10,000 to each student to support learning needs; applying learning using video media; and full support from parents.